Engaging hospital patients in the medication reconciliation process using tablet computers. (4th September 2018) - Prey, Jennifer E; Polubriaginof, Fernanda; Grossman, Lisa V; Masterson Creber, Ruth; Tsapepas, Demetra; Perotte, Rimma; Qian, Min; Restaino, Susan; Bakken, Suzanne; Hripcsak, George; Efird, Leigh; Underwood, Joseph; et al.
Abstract: Objective: Unintentional medication discrepancies contribute to preventable adverse drug events in patients. Patient engagement in medication safety beyond verbal participation in medication reconciliation is limited. We conducted a pilot study to determine whether patients' use of an electronic home medication review tool could improve medication safety during hospitalization. Materials and Methods: Patients were randomized to use a tool before or after hospital admission medication reconciliation to review and modify their home medication list. We assessed the quantity, potential severity, and potential harm of patients' and clinicians' medication changes. We also surveyed clinicians to assess the tool's usefulness. Results: Of 76 patients approached, 65 (86%) participated. Forty-eight (74%) made changes to their home medication list [ before : 29 (81%), after : 19 (66%), p  =   .170]. Before group participants identified 57 changes that clinicians subsequently missed on admission medication reconciliation. Thirty-nine (74%) had a significant or greater potential severity, and 19 (36%) had a greater than 50-50 chance of harm. After group patients identified 68 additional changes to their reconciled medication lists. Fifty-one (75%) had a significant or greater potential severity, and 33 (49%) had a greater than 50-50 chance of harm. Clinicians reported believing that the tool would save time, and patients would supply useful information. Discussion: The results demonstrate a high willingness of patients to engage in medication reconciliation, and show that patients were able to identify important medication discrepancies and often changes that clinicians missed. Conclusion: Engaging patients in admission medication reconciliation using an electronic home medication review tool may improve medication safety during hospitalization.